Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1166/jnn.2013.7502
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solar Cells Using a ZnO/Cu/ZnO Anode Deposited by Ion Beam Sputtering at Room Temperature for Flexible Devices

Abstract: The development of indium-free transparent conductive oxides (TCOs) on polymer substrates for flexible devices requires deposition at low temperatures and a limited thermal treatment. In this paper, we investigated the optical and electrical properties of ZnO/Cu/ZnO multi-layer electrodes obtained by ion beam sputtering at room temperature for flexible optoelectronic devices. This multilayer structure has the advantage of adjusting the layer thickness to favor antireflection and surface plasmon resonance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…然 而, 在应用时人们注意到该定义中R S 所占权重过大, 使得薄膜最大的F值只在相对较大的膜厚和低T的情 况下才能获得. 为此, Haacke [17] 提出用T 10 24,25,47] , Au [28~30] , Cu [31,48] , Al [32,49] , Pd [33] , Pt [50] , Mo [34] , Ni [35] , In [36] 以及一些金属合金 [37,51] 等, 其中用 ,48] , 但 其 最 大 透 过 率 一 般 出 现 在 550~600 nm附近, 与使用Ag作为中间层的TCF相比, 其在500 nm波长附近的光透过率明显更低. 这是由 于Cu和Au具有比Ag更小的等离子体频率, 使其在可 见光的短波长区域具有更强的光吸收 [58,59] .…”
Section: Tcf的表面电阻(r S )和光透过率(T)是衡量其光unclassified
See 1 more Smart Citation
“…然 而, 在应用时人们注意到该定义中R S 所占权重过大, 使得薄膜最大的F值只在相对较大的膜厚和低T的情 况下才能获得. 为此, Haacke [17] 提出用T 10 24,25,47] , Au [28~30] , Cu [31,48] , Al [32,49] , Pd [33] , Pt [50] , Mo [34] , Ni [35] , In [36] 以及一些金属合金 [37,51] 等, 其中用 ,48] , 但 其 最 大 透 过 率 一 般 出 现 在 550~600 nm附近, 与使用Ag作为中间层的TCF相比, 其在500 nm波长附近的光透过率明显更低. 这是由 于Cu和Au具有比Ag更小的等离子体频率, 使其在可 见光的短波长区域具有更强的光吸收 [58,59] .…”
Section: Tcf的表面电阻(r S )和光透过率(T)是衡量其光unclassified
“…通过使用比相应金属具有更大介电常 数的介质层, 可以抑制介质/金属界面的SP耦合的发 生, 因此, 使用更大介电常数的介质材料通常可增加 多层膜的光透过率 [63] . [28,48] , TiO 2 [24] , ZnS [38] , WO 3 [25] 和MoO 3 [32] 等 , TCO 材 料 有 ITO [18,35,60] , AZO [28,33,34,51] , IZO [18] , IGZO [19] , MTO [20] , FTO [21] , 掺镓氧化锌(GZO) [50] 等, 这些TCO一般都是n型的; 但一些p型材料也可以使 用 , 比 如 CuAlO 2 [22] . 此 外 , 有 机 透 明 导 电 材 料…”
Section: Tcf的表面电阻(r S )和光透过率(T)是衡量其光unclassified
“…The deposition technique mainly used for obtaining thin layers are similar to the ones for ITO; thus, magnetron sputtering is the main one [125][126][127]. Other methods for depositing TCOs, include PLD [123,[128][129][130][131], ion beam sputtering [122,132], and pulsed filtered cathodic arc deposition [124].…”
Section: Indium Tin Oxide Filmsmentioning
confidence: 99%
“…Therefore, multilayer structure films based on metal Cu have become a research trend. Among the doped ZnO, AZO (Al-doped ZnO) has better conductivity. Domestic and foreign scholars have widely studied the ZnO/Cu/ZnO structure, but there are relatively few studies on the AZO/Cu/AZO structure, and verification work in simulation has not been reported. The combination of transparent and conductive AZO and cheap Cu has important research significance.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the addition of top and bottom ZnO layers can lead to the shift of the peak transmittance of the Ag layer to the visible wavelength, improve the transmittance and spectral uniformity of the electrode, and the thickness change of the top ZnO layer plays a leading role in the transmittance. Himadri Sekhar Das 12 In conclusion, internal and external scholars have made a number of analysis on the use of silver (Ag), 15,16 copper (Cu), 17,18 aluminum (Al), palladium (Pd), gold (Au), 19 molybdenum (Mo), 20,21 and nickel (Ni). 22 The AZO/Cu/AZO structure has many advantages over its TCO/metal/TCO structure; for example, AZO has excellent optical transmittance, and its conductivity is better than ZnO.…”
Section: Introductionmentioning
confidence: 99%